2022
DOI: 10.1007/s00586-022-07137-7
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of anterior surgical decompression surgery for cervical degenerative disk disease: a systematic review of economic evaluations

Abstract: Purpose No clear consensus exists on which anterior surgical technique is most cost-effective for treating cervical degenerative disk disease (CDDD). One of the most common treatment options is anterior cervical discectomy with fusion (ACDF). Anterior cervical discectomy with arthroplasty (ACDA) was developed in an effort to reduce the incidence of clinical adjacent segment pathology and associated additional surgeries by preserving motion. This systematic review aims to evaluate the evidence reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…cervical disk replacement or posterior cervical fusion). 18 Only two studies by Martin et al 19 and Safaee et al 20 have reported cost in the outpatient setting, but both specifically excluded the ambulatory setting. This report thus represents the first and only cost-effectiveness Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cervical disk replacement or posterior cervical fusion). 18 Only two studies by Martin et al 19 and Safaee et al 20 have reported cost in the outpatient setting, but both specifically excluded the ambulatory setting. This report thus represents the first and only cost-effectiveness Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Most cost-effectiveness studies in the literature compare ACDF to other cervical procedures (e.g. cervical disk replacement or posterior cervical fusion) 18. Only two studies by Martin et al 19 and Safaee et al 20 have reported cost in the outpatient setting, but both specifically excluded the ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the proposed study is cost-effectiveness. No difference in QALYs is expected between the intervention and control group based on previous literature 41 .…”
Section: Power Considerationsmentioning
confidence: 80%
“…However, not all aspects have been su ciently investigated. Only few studies have investigated the cost-effectiveness between techniques, although not in such an extensive, prospective, randomized controlled trial 41,94 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation